2021
DOI: 10.21608/mid.2021.82048.1165
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Colistin Resistant E. coli in Children at Pediatric Hospital of Assiut University, Using Phenotypic and Genotypic Methods

Abstract: Background:The emergence of colistin-resistant strains is considered a great threat for the children suffering from diarrhea. This study aimed to screen for the presence of mcr-1 in Escherichia coli (E. coli) isolates collected from children with diarrhea and to compare between genotypic and phenotypic methods for detection of colisitin resistant E.coli carrying mcr-1gene. Methods: Isolation of E.coli was done followed by antimicrobial susceptibility test. Kirby-Baur disc diffusion was used to determine antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…By investigating plasmid mediated mcr-1, we detected it in 94.4% of colistin resistant strains (all colistin resistant E.coli and 93.3% of colistin resistant K. pneumoniae) which is a very high percentage in comparison with other studies done in Egypt and worldwide. In Egypt, Ghandour et al reported 35.78% of E. coli isolates were positive for mcr-1 [25]. Zafer et al declared that only 5% of isolates obtained mcr-1 (E. coli and K. pneumoniae) [22] [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…By investigating plasmid mediated mcr-1, we detected it in 94.4% of colistin resistant strains (all colistin resistant E.coli and 93.3% of colistin resistant K. pneumoniae) which is a very high percentage in comparison with other studies done in Egypt and worldwide. In Egypt, Ghandour et al reported 35.78% of E. coli isolates were positive for mcr-1 [25]. Zafer et al declared that only 5% of isolates obtained mcr-1 (E. coli and K. pneumoniae) [22] [26,27].…”
Section: Discussionmentioning
confidence: 99%